The right to image: how self-management and legal literacy shape a responsible PR professional - Ryabovolyk, Tetiana; Lypchanskyi, Volodymyr; Kramar, Bohdan (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article explores the interconnection between self-management and legal literacy of PR professionals as key factors in shaping professional responsibility and a sustainable image in the digital era. It analyses current legal requirements for public communication, including copyright compliance, personal data protection, and liability for disseminating fake information. The importance of individual legal culture is emphasized as a tool for minimizing reputational risks. Practical recommendations are proposed on how to combine legal awareness with effective self-management strategies in the field of public relations. The purpose of the article is to investigate the role of self-management and legal literacy in shaping a responsible PR specialist within the modern information landscape. In particular, the significance of legal awareness as an instrument for minimizing professional and reputational risks is substantiated, as well as the potential of self-management in upholding ethical standards in public communication. To achieve this goal, the research employed methods of analysis and synthesis, comparative legal method, generalization and systematization, logical and dialectical methods, content analysis, and a systematic approach.

У статті розглянуто взаємозв’язок між самоменеджментом та юридичною обізнаністю PR-фахівця як ключовими чинниками формування професійної відповідальності та сталого іміджу в цифрову епоху. Проаналізовано сучасні правові вимоги до публічної комунікації, зокрема дотримання авторських прав, захист персональних даних, відповідальність за поширення фейкової інформації. Наголошено на важливості особистої правової культури як інструменту мінімізації репутаційних ризиків. Запропоновано практичні рекомендації щодо поєднання правової грамотності з ефективними стратегіями самоменеджменту у сфері зв’язків з громадськістю. Метою статті є дослідження ролі самоменеджменту та юридичної грамотності у формуванні відповідального PR-фахівця в умовах сучасного інформаційного простору. Зокрема обґрунтовано значення правової обізнаності як інструменту мінімізації професійних та репутаційних ризиків, а також розкрити потенціал самоменеджменту для дотримання етичних стандартів у сфері публічної комунікації. Для досягнення поставленої мети використано методи аналізу та синтезу, порівняльно-правовий метод, узагальнення та систематизації, логічний та діалектичний методи, контент-аналіз та системний підхід.
Право на імідж: як самоменеджмент та юридична грамотність формують відповідального PR-фахівця
Keywords: PR specialist; self-management; legal literacy; professional responsibility; ethical standards; legal aspects; public relations; PR-фахівець; самоменеджмент; юридична грамотність; професійна відповідальність; етичні стандарти; правові аспекти; зв'язки з громадськістю